Regulação e planejamento urbano-ambiental em processos de suburbanização: o caso do projeto CSul Lagoa dos Ingleses, RMBH - Fernanda Lima Bandeira de Mello (2022)
Considering the connection between processes of suburbanization and large urban projects in the Metropolitan Region of Belo Horizonte (RMBH), this dissertation aims to investigate the deliberation and approval process of the Centralidade Sul (CSul) project, a large-scale centrality proposal located in the municipality of Nova Lima, within the scope of public institutions responsible for urban-environmental planning and regulation. For that, the methodological instruments chosen included bibliographic and documentary research, interviews with public agents, visits in site in order to identify territorial transformations in progress and, finally, a survey of the marketing strategies adopted by the project's entrepreneurs. The theoretical framework adopted considered studies by authors linked to the fields of political economy of urbanization, contemporary urban and regional planning, suburbanization, and large urban projects. The process of formation of the “urban fabric” through the implosion and explosion of cities, from the Industrial Revolution, led to the formation, on the edges of cities, of disjoint fragments, fractals and suburbs. Currently, the economic restructuring processes underway since the mid-1980s have caused profound changes in the urban field. Among them, the then emerging current of urban entrepreneurship is guided by the alliance between strategic sectors to enable iconic architectural projects that guarantee high locational gains. The CSul project emerges as an example of these new structures, but endowed with uniqueness in terms of its significant extent compared to other projects proposed and implemented in the RMBH since the mid-2000s. The coalition between agents endowed with different forms of capital seems to ensure the approval of the project without major obstacles, despite significant contradictions found throughout its environmental licensing process. With an urban project designed by Jaime Lerner’s architecture office, CSul aims to establish itself, according to its entrepreneurs, as the largest urban development project in Latin America and, for that, it has adopted urban marketing strategies to attract new developments and activities related to cutting-edge technology sectors, as well as real estate segments for the high-income population. At the same time, informal settlements, such as the Água Limpa neighborhood, proliferate in its surroundings and are ignored by the project. Analyzing the urban process under capitalism, through the CSul case study, allows us to understand how the production of urban space takes place in contemporary times.